Onlay Rib Bone Graft in Elevation of Reconstructed Auricle: 17 Years of Experience - Taehoon Kim; Jihyeon Han; Yoonho Lee (Archives of Plastic Surgery, 2013)
Background  A cartilage wedge block and covering flap are standard procedures for firmelevation of the ear in microtia correction. However, using costal cartilage for elevation ofthe reconstructed auricle can be insufficient, and the fixed cartilage wedge block may beabsorbed or may slip out. Furthermore, elevating covering flaps is time-consuming and usesup fascia, a potential source of reconstruction material. Therefore, we propose an innovativemethod using autologous onlay rib bone graftfor auricular elevation ofmicrotia.Methods  From February 1995 to August 2012, 77 patients received a first stage operationwith a rib cartilage framework graft. In the second stage operation, a small full thickness ofrib bone was harvested through the previous donor scar. The bihalved rib bone was insertedinto the subperiosteal pocket beneath the cartilage framework.Results  The follow-up time ranged from 1 month to 17 years, with a mean of 3 years. Allof the patients sustained the elevation of their ears very well during the follow-up period.Donorsite problems, exceptfor hypertrophic scars,were not observed. Surgery-related complications,specifically skin necrosis, infection, or hematoma, occurred in 4 cases.Conclusions  Onlay rib bone graft used to elevate the reconstructed auricle is a more anatomically appropriate materialthan cartilage, due to the bone-to-bone contact between thebone graft and the temporal bone. Postoperative minor correction of the elevation degree isstraightforward and the skin graft survives better. Therefore, reconstructed auricle elevationusing onlay rib bone graftis a useful and valuablemethod.